Simultaneous Hodgkin lymphoma and BRAFV600E-positive papillary thyroid carcinoma: A case report. Issue 3 (January 2019) - Liu, Shu; Zhao, Yanru; Li, Miaojing; Xi, Jieying; Shi, Bingyin; Zhu, Huachao
Abstract: Rationale: Papillary thyroid carcinoma (PTC) is the most common endocrine malignancy. However, the simultaneous occurrence of PTC and Hodgkin Lymphoma (HL) was rarely reported. Patient concerns: We present a case of simultaneous BRAF V600E - positive PTC and HL in a 17-year-old female. Diagnosis: She was referred to our clinic with a painless lump in her left neck. A highly suspicious thyroid nodule and multiple enlarged lymph nodes in the neck were found by ultrasonography examination. The suspicious nodule was diagnosed as PTC by fine needle aspiration cytology. Interventions: A total thyroidectomy with bilateral lymph node dissection was performed and the microscopic examination revealed a 2-cm PTC with BRAF V600E mutation and HL (mixed cellularity) in the bilateral lymph nodes. PTC was postoperatively considered as T1bN0M0. Levothyroxine (125 μg/d) was administered to the patient for thyrotropin suppression therapy. Then the patient was referred to the Department of Hematology to receive 4 cycles of ABVD followed by 30 Gy involved-site radiotherapy and radioactive iodine (RAI) therapy for thyroid cancer. Outcomes: After two cycles of ABVD, multiple enlarged lymph nodes showed a significant response to the chemotherapy in the patient. Lessons: Simultaneous HL and BRAF V600E -positive PTC is extremely rare. Biopsy of the suspicious lymph nodes should be performed to confirm malignancy metastasizing from PTC or other lesions. Similarly, in HL patients with suspicious thyroid nodule, ultrasound-guided fine needle aspiration of thyroid nodule should be performed to exclude thyroid malignancy.